Histórias cruzadas: reconstrução socio-histórica do badminton da Paraíba e do Piauí - Silva, Everton Pereira da (2020)
Badminton is a sport on the rise in Brazil, such context has boosted our research interest involving this sport. Our goal is to discuss how the sport is characterized in the different states of the northeast. For this study we chose Paraíba and Piauí. Our objectives are: A) To describe and analyze the reports of social actors that were part of the socio-historical formation process of badminton of Paraíba and Piauí; B) Identify similarities and differences between the socio-historical processes of Badminton in these states. The study is characterized as a qualitative research that uses the perspective of discourse analysis in the French line for analysis of the interviews. The research will understand the paths traced by Badminton practitioners from Paraíba do Piauí in the hope of contributing to the crossing of narratives to reveal aspects of approximation and distance between the practices of this sport in the two states.